Adaptive cancellation of light relative intensity noise for fiber optic gyroscope - Zhong xiao Ji (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to reduce the relative intensity noise (RIN) in the interferometric signal of the fiber optic gyroscope (FOG), an adaptive noise subtraction method is presented, which aims to overcome to the drawbacks that the fixed delay time and gain of the digital noise subtraction method. The drawbacks will make the performance of FOG to be degraded greatly in the changing environment. In the paper the adaptive noise subtraction system based on the recursive least squares algorithm (RLS) is formed in FPGA, in which the interferometric signal is regarded as the signal source, and RIN in the free end of the optical fiber coupler of FOG is looked as the noise reference signal. The two critical parameters that minimum delay time and its varying range result from measuring the minimum and maximum delay times of the interferometric signal in a certain temperature range. The off-line and on-line temperature experimental results verify the capability of adapting to the environmental temperature. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3373